CHARACTER EDUCATION FOR EARLY CHILDHOOD: TO PREVENT JUVENILE DELINQUENCY AND THE NEGATIVE IMPACTS OF GADGET USE IN INDONESIA - Jailani, Mohammad (The Ministry of Religious Affairs, The Republic of Indonesia, 2023)
The rise of juvenile delinquency, klitih, and good pornography circulating on social media, television broadcasts, news reports. This is because children and adolescents to adults lack character education and assistance (guidance) from the closest people and parents. The purpose of this study is to describe early childhood or those seen from the point of view of character education in Islamic education. As an anticipation of the negative impacts of gadgets, handponds, and gedged. This research is based on literature review. This type of research uses a literature review. Data is generated or obtained through literature data, books, journals, and online news exposures. Data collection techniques come from primary data, secondary data, and reference sources from books and journals that are relevant to the research theme. The data analysis technique uses content analysis of the contents of the literature research. The results of the study found that there were elements and motives for juvenile delinquency, children could not be directed and managed by their parents, it was difficult for their teachers and parents to regulate and guide them. There is content that is not useful, as well as sites that are not good. This is due to the low and weak character education and guidance of Islamic education for children. The importance of being selective and smart in social media. The implications of this research are character building and guidance in the perspective of Islamic education.